The Strength of Private Agreements on the Division of Joint Assets Before Divorce and Their Consequences in Joint Asset Claims - Intan Alpidoh; Lia Amaliya; Muhamad Abas (PT. Anagata Sembagi Education, 2024)
The purpose of a marriage bond is to form a household that is sakinah mawadah warrahmah that lasts until the end of life. However, often this goal cannot be realized due to various kinds of conflicts in a marriage bond that eventually results in divorce. The end of the marital relationship due to divorce does not necessarily solve problems between divorced husband and wife, sometimes new conflicts arise after the occurrence of divorce, including regarding common property that is contested through a Joint Property Lawsuit. One way to anticipate the emergence of such conflicts is to make a Prenuptial Agreement that is carried out before marriage. The problem is what if the agreement is made before the divorce and how the strength of the joint property division agreement made before the divorce is reviewed from the Civil Code against the joint property lawsuit. Qualitative Research Method Using the Normative Juridical Approach Method. The result of his research is the evidentiary power of the agreement on the division of common property carried out under the hands before the divorce reviewed from article 1338 of the Civil Code and article 1320 of the Civil Code which guarantees the legal force of the agreement made before the divorce in the joint property lawsuit and also whether the agreement under the hands can be said to have perfect evidentiary power as per the principle of pacta sunt servanda.